2019
DOI: 10.3390/jcm8111935
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity of Diabetic Foot Ulcers: Current Status and Future Prospectives

Abstract: Diabetic foot ulcers (DFUs) and diabetic foot infections (DFIs) are associated with reduced patient quality of life, lower-extremity amputation, hospitalization, and high morbidity and mortality. Diverse bacterial communities have been identified in DFUs/DFIs, playing a significant role in infection prognosis. However, due to the high heterogeneity of bacterial communities colonized in DFUs/DFIs, culture-based methods may not isolate all of the bacterial population or unexpected microorganisms. Recently, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 65 publications
3
65
1
Order By: Relevance
“…Progression of DFIs to more complicated scenarios, such as minor and major amputation of a lower limb occurs every 30 s in the world which can influence the quality of life in many diabetic people worldwide 1 . Identification of pathogenic bacteria is the first essential step to monitor and control the etiology of DFIs accurately (Sadeghpour Heravi et al, 2019). However, a large portion of bacterial species are not culturable using traditional methods (Suryaletha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progression of DFIs to more complicated scenarios, such as minor and major amputation of a lower limb occurs every 30 s in the world which can influence the quality of life in many diabetic people worldwide 1 . Identification of pathogenic bacteria is the first essential step to monitor and control the etiology of DFIs accurately (Sadeghpour Heravi et al, 2019). However, a large portion of bacterial species are not culturable using traditional methods (Suryaletha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of pathogenic bacteria is the first essential step to monitor and control the etiology of DFIs accurately ( Sadeghpour Heravi et al, 2019 ). However, a large portion of bacterial species are not culturable using traditional methods ( Suryaletha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…low permeability to antibodies and neutrophils) and antibiotics. GBS has been reported as a prevalent microorganism in DFUs (8). However, the most common pathogen in DFU (with or without osteomyelitis) is S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a wound model has shown that when grown in culture together, P. aeruginosa and S. aureus display an enhanced antibiotic tolerance [ 60 ]. Bacteroides fragilis has been reported in several studies as the predominant anaerobic bacteria isolated in DFIs [ 61 – 63 ], and is also important in community dynamics and biological interactions. Mastropaolo et al [ 64 ] demonstrated the effect of polymicrobial infection involving Escherichia coli , Bacteroides fragilis , and Clostridium perfringens in a mouse model of type 2 diabetes.…”
Section: The Dynamic Dfu Microbiomementioning
confidence: 99%